Greenhouse gas emissions in the countries of the Visegrad Group: an analysis of sustainable agriculture and environmental management - Bartl, Bianka; Soós, Gábor; Stankovics, Petra; Simon-Gáspár, Brigitta (GEORGIKON FOR AGRICULTURE, 2022)
Our study analyses the greenhouse gas emission intensity of the main agricultural products in the Visegrad Four. The time interval under consideration is 2000-2017. According to the statistical calculation, the GHG emission intensity of the production of the Visegrad Group’s agricultural products was similar for most of the products that we examined. In the case of lamb production and egg production, we found significant differences between the countries emission data. All countries except the Czech Republic have reduced their emissions in respect of the production of cereal products, with the same variability. We have observed a steady decline in pork production emissions in all member states except Slovakia. All countries have reduced GHG emissions intensity in terms of emissions related to the production of cow's milk. Differences between countries can be due to the differences in the market conditions and the different structures of agricultural sectors of the four member states.
Keywords: Visegrad Four; agri-environment; emissions intensity